Glycemic Status of Type 2 Diabetic Patients Treated with Different Single Anti-diabetic Agents (BIRDEM Medical Journal, 2016)
Objective: The study was aimed to describe the patterns of single anti-diabetic agents used by type 2 diabetic patients and their glycemic status during hospital admission.Study design and methods: This cross-sectional study was carried out in BIRDEM among hospitalized type 2 adult diabetic patients of different ages and both sexes. Data were collected during admission that included detailed history, medical records review, clinical examination and laboratory investigations.Results: Subjects (n=253; 174 female, 79 male) had age (years) as mean ± SD: 55.28 ±13.45 (15- 90 years), BMI (kg/m2) as mean ±SD: 24.67±4.97 and HbA1c (%) as mean ±SD: 10.56±2.98. Use of pre-mixed insulin 90 (35.57%) and split-mixed insulin 70 (27.66%) were more common than other drugs. Glycaemic control was poor in all age groups as evidenced by raised HbA1c, significantly higher in patients